THE PRINCIPLE OF MAQASHID SHARIA IN THE RECRUITMENT, SELECTION, AND PLACEMENT PROCESSES OF EDUCATORS AT PESANTREN PERSIS 67 BENDA - Rasyid, Hilman; Pane, Fadhilah Anggraini; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The principles of Maqashid Syariah, encompassing the preservation of religion (hifdz ad-din), life (hifdz an-nafs), intellect (hifdz al-aql), lineage (hifdz an-nasl), and wealth (hifdz al-mal), are applied holistically to establish an Islamic education system that meets modern needs. This study aims to analyze the implementation of Maqashid Syariah principles at Pesantren Persis 67 Benda, focusing on preserving religious, intellectual, moral, and social values in the management of educators. Using a qualitative approach and phenomenological method, data were collected through in-depth interviews, observations, and document analysis involving pesantren leaders, recruitment teams, and teachers. The findings reveal that Maqashid Syariah principles are applied in three main stages. In the recruitment process, emphasis is placed not only on meeting administrative criteria but also on moral integrity, religious competence, and pedagogical skills, with a preference for alums of the pesantren. During the selection process, a comprehensive evaluation is conducted through religious tests, interviews to assess commitment to Islamic values, teaching simulations to ensure instructional quality, and administrative reviews to guarantee equal opportunities for all applicants. In the placement process, educators are assigned based on the alignment of their competencies with the needs of the pesantren, teacher welfare, and their contribution to students' character development.